1996
DOI: 10.1088/0960-1317/6/1/033
|View full text |Cite
|
Sign up to set email alerts
|

Modelization and characterization of asymmetrical thermal micro-actuators

Abstract: Structures of very high aspect ratio which are mechanically stiff in the substrate direction and flexible in the direction parallel to the substrate are studied. Such structures can be exploited to produce thermal flexure actuators which are capable of large motion produced by thermal expansion. The magnitude of the deflection depends strongly on geometry and material properties. Structures fabricated by laser micro-machining are characterized and compared to numerical simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 3 publications
1
54
0
Order By: Relevance
“…A class of new active end-effectors based on an E-T actuation principle was introduced in our earlier work [7,11]. The performance of E-T actuators is limited by the maximum operating temperature and thermal stresses [12][13][14]. The coupling of "E-T to structural" is much stronger than the "structural to E-T" coupling.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…A class of new active end-effectors based on an E-T actuation principle was introduced in our earlier work [7,11]. The performance of E-T actuators is limited by the maximum operating temperature and thermal stresses [12][13][14]. The coupling of "E-T to structural" is much stronger than the "structural to E-T" coupling.…”
Section: Open Accessmentioning
confidence: 99%
“…The multi physics simulation of thermal MEMS actuators is often obtained from Finite Element Modeling (FEM) or Finite Element Approximation (FEA). Lerch et al have studied the temperature distribution and deflection of a microstructure using a Finite Element (FE) analysis [12]. Lin and Chiao have used FE simulation to study the E-T response of a line-shape microstructure [8].…”
Section: Open Accessmentioning
confidence: 99%
“…The shape factor of heat conduction shape, S, (Lerch et al 1996) impacts the shape of the element on the excessive heat conduction to the substrate. The shape factor is defined by the total heat flux out of the line shaped microstructure per unit length divided by heat flux going directly under the width of a microstructure (Lin and Chiao 1996).…”
Section: General Heat Conduction Theorymentioning
confidence: 99%
“…Lin and Chiao (1996) used finite element (FE) simulation to study the electrothermal response of line shaped microstructures. Lerch et al (1996) reported the FE analysis of a thermal microactuator for maximum temperature in the device. Mankame and Ananthasuresh (2001) introduced a comprehensive thermal model for an electrothermal complaint microactuator studied by FE simulation.…”
Section: Introductionmentioning
confidence: 99%
“…These strains deflect and rotate the free end of the device. With careful design, either the linear or the angular component may be enhanced [7]. To enhance the latter, differences in arm length are more appropriate than variations in arm width [8].…”
Section: Index Terms-microelectromechanical Systems (Mems) Microoptomentioning
confidence: 99%